THE CHARACTER ANALYSIS OF GLEN HANSARD IN ONCE FILM - Nani Rosnani Thamrin; Baran Wargika (English Review: Journal of English Education, 2013)
Abstract: This paper analyzed the characterization of talented actor named Glen Hansard in Once film. This study employed a descriptive qualitative research design based on theories of Rahardjo (1985), Robert (1965), and Card (1988). Primary data sources were whole Once scenes film directed by John Carney which had low-budgeting production with two stars, Glen Hansard and Irglova, while secondary data sources were collected from the articles related to this study. This research mainly investigated two aspects involved two character analyses of the main actor, Hansard. The first one was the construction of Hansard’s characters and the second one was the effect between his character and another actors’ character. The study showed that Hansard’s characters were constructed by five factors: from what the character did and said, what the other characters said about him, how the appearance and its milieu were, influencing one and  another.The study also found that he had struggle, visionary, ambitious, introvert, sensitive, straightforward and curious characters, but more characters that showed strong characters of his were struggle, visionary and ambitious, because the scenes reflected them more.Keywords: literary works, film, character, characterizing.